The Negative consumerism for female students in the College of Home Economics at King Khalid University and its relationship to studying home economics - Ali, Abeer Abdo Muhammad (Journal of Economic, Administrative and Legal Sciences, 2022)
The research aims to study the relationship between the negative consumerism of university youth and the study of the fields of home economicsThis study was conducted on a sample of (60) female students from the Faculty of Home Economics، and the sample was taken in a purposive، coincidental way، and took place in the second semester of the year 1441 AH. Nutrition- clothes- housing), and a questionnaire to measure the negative consumerism of university youthThe most important results concluded that there is a positive correlation between each of the negative consumerism as a whole with its axes and the study of the fields of home economics. There are also statistically significant differences between the negative consumerism of university youth and the study of home economics، according to the difference in the educational level of the parents (mother- father). The most important recommendations were the necessity of providing some degree of economic education، because it plays a role in shaping the economic and saving behavior of young people (economic knowledge).
Keywords: Negative consumerism; areas of home economics